Nano Tips to Streamline Work Tasks Using Microsoft Copilot with Lachezar Arabadzhiev. - Arabadzhiev, Lachezar (linkedin.com, 2024)
Get quick, bite-sized tips on using Microsoft Copilot to streamline work tasks. Each video is less than two minutes long, so you can make learning fit into even your busiest days.